2012
DOI: 10.1108/02634501211211975
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to internationalisation in SMEs: evidence from Jordan

Abstract: Purpose -This study aims to identify some of the major barriers that may hinder potential small to medium-sized enterprise (SME) exporters and non-exporters from exporting their operations in the international market. Design/methodology/approach -Based on the aim of this study, a questionnaire based survey method was conducted among 250 Jordanian manufacturing SMEs using random sampling with usable response rate of 54 per cent. Data were analysed using relevant statistical methods ranging from factor analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 43 publications
4
117
2
1
Order By: Relevance
“…OECD (2006) has reported that duration for developing countries to complete the process of either exporting or importing is three times higher than developed countries. Despite the critical role of express service to facilitate internationalisation of SMEs, earlier studies failed to identify this as a key barrier for SME internationalisation process (Al-Hyari, Al-Weshah and Alnsour, 2012;Okpara and Kabongo, 2010). In the light of above, it has been hypothesized that: H6: Lack of express service within the home economy would work as a barrier for SMEs to enter into foreign market.…”
Section: Please Insert Figure 1 Herementioning
confidence: 99%
“…OECD (2006) has reported that duration for developing countries to complete the process of either exporting or importing is three times higher than developed countries. Despite the critical role of express service to facilitate internationalisation of SMEs, earlier studies failed to identify this as a key barrier for SME internationalisation process (Al-Hyari, Al-Weshah and Alnsour, 2012;Okpara and Kabongo, 2010). In the light of above, it has been hypothesized that: H6: Lack of express service within the home economy would work as a barrier for SMEs to enter into foreign market.…”
Section: Please Insert Figure 1 Herementioning
confidence: 99%
“…Thus, nothing is more important than CEOs' choices to enter into new international markets. That is to say, this study suggests that the CEO's global orientation plays an important role in promoting rapid internationalisation [62]. Finally, it implies that in export-oriented countries such as South Korea, successful internationalisation is needed to have national competitiveness, suggesting that investigating the characteristics of INVs, that have played an essential role in improving the competitiveness, is significant and meaningful for both academia and industry that would like to carry out the successful internationalisation.…”
Section: Summary and Implicationsmentioning
confidence: 78%
“…Therefore, this study has a significant implication that proposes a research direction that various technological characteristics can affect internationalisation, and these characteristics should be studied more comprehensively. In the case of SMEs like INVs, it is very difficult to internationalise due to limited resources [62]. Thus, nothing is more important than CEOs' choices to enter into new international markets.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…At least there are two factors that lead the low of SMEs export performance so that lower the value of its contribution to the total national exports [2]. Both of these obstacles are internal and external constraints.…”
Section: Introductionmentioning
confidence: 99%
“…The internal constraints related to access with information about foreign markets, functional ability/managerial facing foreign markets, and marketing. While external factors associated with export procedures, the role of government, the difficulties facing foreign competitors and customers, and the differences in the economic, political, and social culture [2], [3].…”
Section: Introductionmentioning
confidence: 99%